2014
DOI: 10.1038/nutd.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to the endocrine disruptor di-(2-ethylhexyl) phthalate promotes local adipose and systemic inflammation in adult male offspring

Abstract: Background:Di-(2-ethylhexyl) phthalate (DEHP) is a plasticizer used to increase the flexibility of polyvinyl chloride. DEHP and its active metabolite mono-(2-ethylhexyl) phthalate are detected in many biological fluids during fetal and postnatal life. In rodent models, in utero DEHP exposure has been shown to alter sexual organ development, decrease testosterone and aldosterone production, increase body and epididymal adipose tissue weight, and raise serum lipids and glucose levels in male offspring.Objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 62 publications
2
43
0
Order By: Relevance
“…Moreover, di(2-ethylhexyl) phthalate (DEHP) or its metabolite mono-(2-ethylhexyl) phthalate (MEHP) increased adipocyte differentiation in 3T3-L1 cells, (142) (115), murine mesenchymal stem cells (44), and in vivo (142) (62). Few human studies have addressed effects of BFRs on obesity and metabolic syndrome; however, adipocyte differentiation was increased by the BFRs PDBE (397) and BDE-47 (185).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…Moreover, di(2-ethylhexyl) phthalate (DEHP) or its metabolite mono-(2-ethylhexyl) phthalate (MEHP) increased adipocyte differentiation in 3T3-L1 cells, (142) (115), murine mesenchymal stem cells (44), and in vivo (142) (62). Few human studies have addressed effects of BFRs on obesity and metabolic syndrome; however, adipocyte differentiation was increased by the BFRs PDBE (397) and BDE-47 (185).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…Campioli et al [83] found that in utero exposure of Sprague Dawley rats to DEHP resulted in increased adipose tissue inflammatory markers (e.g., TNF-α) across several doses, and this association was also reflected in the serum of offspring at the highest exposure dose. In addition, gene expression analysis showed alteration in both immune response and inflammatory-associated genes.…”
Section: Phthalatesmentioning
confidence: 96%
“…One possible mechanism by which prenatal environmental exposures may influence childhood or adult disease risk is through epigenetic modifications [189], mitotically heritable changes to DNA that affect subsequent gene expression. Another possible mechanism is through the promotion of adipocyte differentiation or proliferation at critical periods of development [196]. More research is needed to elucidate the role of in utero exposure to environmental chemicals in altering adult s usceptibility to chronic disease.…”
Section: Prenatal Environmental Exposures and Epigenetic Influences On mentioning
confidence: 99%